PENGARUH PROMOSI DAN PELAYANAN TERHADAP KEPUASAN PELANGGAN DI TOKO MOISELLE PATISSERIE - Yosua Parhorasan Manullang; Jessica (Adisam Publisher, 2024)
This research aims to determine the effect of promotion and service on customer satisfaction at the Moiselle Patisserie Medan Shop. The population in this study is the number of customers in the last month, namely 232 customers of the Moiselle Patisserie Medan Shop who made purchases directly or online in September 2022. In looking for samples, researchers used the slovin sampling technique. Based on calculations, the sample used by researchers after rounding was 70 at the Moiselle Patisserie Medan Shop. The research results show that promotions partially have a positive and significant effect on customer satisfaction at the Moiselle Patisserie Medan Store. Service partially has a positive and significant effect on customer satisfaction at the Moiselle Patisserie Medan Shop. Promotion and service simultaneously have a positive and significant effect on customer satisfaction at the Moiselle Patisserie Medan Shop.